Thinking the limits of the body - Cohen, Jeffrey Jerome; Weiss, Gail, 1959- (State University of New York Press, 2003)
This collection maps the very best efforts to think the body at its limits. Because the body encompasses communities (social and political bodies), territories (geographical bodies), and historical texts and ideas (a body of literature, a body of work), Cohen and Weiss seek trans-disciplinary points of resonance and divergence to examine how disciplinary metaphors materialize specific bodies, and where these bodies break down and/or refuse prescribed paths. Whereas postmodern theorizations of the body often neglect its corporeality in favor of its cultural construction, this book demonstrates the inseparability of textuality, materiality, and history in any discussion of the body.
Keywords: Human body -- Social aspects.; Human body (Philosophy); Corps humain -- Aspect social.; Corps humain (Philosophie); SOCIAL SCIENCE -- Anthropology -- Cultural.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Popular Culture.; Human body -- Social aspects